Yeni Türk ticaret kanunu ile tedrici kuruluşun kaldırılması ve kuruluşta payların halka arzı taahhüdü ile halka açılma - (:unkn) unknown (My University, 2013)
Çalışma konumuzu oluşturan “kuruluşta payların halka arzı taahhüdü ile halka açılma” YTTK m. 346’da düzenlenmiştir. Bu yöntemde kuruluş aşamasında pay sahipleri payları taahhüt eder, fakat pay bedellerinin kanu- nen ödenmesi gereken asgari kısmını ödemez. Bu nedenle, TTK m. 346 düzenlemesinin TTK m. 344’deki pay bedellerini ödeme yükümlülüğüne geçici bir istisna getirdiğini söyleyebiliriz. Payları taahhüt eden pay sahip- leri, bu payları şirketin tescilinden itibaren iki ay içinde halka arz etmeyi esas sözleşme ile taahhüt ederler. Taahhüt sahiplerince halka arz edilmesi- ne rağmen süresi içinde satılmayan pay bedellerinin tamamı, halka arz edilmeyen pay bedellerinin ise %25’i iki aylık süreyi izleyen üç gün içinde taahhüt sahiplerince ödenir. TTK m. 346 bu yöntemde payların halka arzı- nın sermaye piyasası mevzuatına göre yapılacağını hüküm altına almakta- dır. Diğer bir deyişle, kuruluşta payların halka arzı taahhüdüyle halka açılma sisteminin işleyebilmesi Sermaye Piyasası düzenlemelerinin bu sisteme işlerlik kazandırmasına bağlı olacaktır.

“Public offering at establishment stage”, which is subject of this study, is regulated in Art. 346 of the New Turkish Commercial Code. In this method, shareholders commit to the shares, but do not pay the mini- mum portion of stock that they legally must pay. As a result, the provision in Art. 346 of the New Turkish Commercial Code establishes a temporary exception to the obligation to pay the stock, which is regulated in Art. 344. The Shareholders who committed the shares must make a public offering of these shares within two months after registration of the company. Whole value of the shares that cannot be sold in time despite the offering by the shareholders and 25% of the value of the shares that have not been offered to the public must be paid by the promisors within three days following the two month period. Art. 346 of the Turkish Commercial Code provides that this method of public offering must be made according to the Regulations of Capital Markets. In other words, efficiency of the system of “public of- fering by promise of public offering at establishment stage” will be de- pendent on the ability of the Regulations of Capital Markets to provide functionality for this system.
Annulment of gradual establishment system by new Turkish commercial code and public offering at establishment stage
Keywords: Hukuk